2012
DOI: 10.1017/s1368980012000833
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status and fish intake of Sudanese schoolchildren living in the Red Sea and White Nile regions

Abstract: AbstractObjectiveTo investigate iodine status and fish consumption of schoolchildren living in the Red Sea and White Nile regions of Sudan.DesignCross-sectional study to determine urinary iodine concentration, visible goitre rate, iodine content of salt and fish consumption. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
(17 reference statements)
1
18
1
Order By: Relevance
“…Twenty-three papers reported cross-sectional studies in children [41, 4364], of which 14 papers mainly reported thyroid diseases [41, 46, 4749, 5155, 56–58, 60], four reported biomarkers [6164] and five described both [43–45, 50, 59] (Tables 5 and 6). Except for Nepal et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-three papers reported cross-sectional studies in children [41, 4364], of which 14 papers mainly reported thyroid diseases [41, 46, 4749, 5155, 56–58, 60], four reported biomarkers [6164] and five described both [43–45, 50, 59] (Tables 5 and 6). Except for Nepal et al .…”
Section: Resultsmentioning
confidence: 99%
“…Water was a cause of excess iodine status in ten papers, from China [4448, 52, 58, 59], refugee camps in Africa [53] and Somalia [41]. USI caused excess intake in five papers, from Sudan [51], Saudi Arabia [49], Uganda [56], refugee camps in Africa [55] and Brazil [54]. Fortified food might have been a cause in two papers, from Sudan [51] and the USA [60], while seafood consumption might have been the cause in one paper from Japan [57].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations